Quercetin: Putative effects on the function of cryopreserved sperms in domestic animals. Issue 2 (16th November 2022) - Abdelnour, Sameh A.; Sindi, Ramya A.; Abd El‐Hack, Mohamed E.; Khalifa, Norhan E.; Khafaga, Asmaa F.; Noreldin, Ahmed E.; Samir, Haney; Tufarelli, Vincenzo; Losacco, Caterina; Gamal, Mohammed; Imam, Mohamed S.; Swelum, Ayman A.
Abstract: Quercetin is one of the most used antioxidant flavonoids and largely exists in many fruits and vegetables because of its capability to scavenge the free reactive oxygen species (ROSs) by repressing lipid peroxy radical fusion, metal ion chelating through enzyme inhibition, and adopting the repair mechanisms. It also exhibits various biological actions, including antioxidative, anti‐inflammatory and antimicrobial activities. Furthermore, it contributes well to sustaining the endogenous cellular antioxidant defence system. The process of cryopreservation is associated with increased oxidative stress, and some steps are potential sources of ROSs, including the method of semen collection, handling, cryopreservation culture media, and thawing, which result in impaired sperm function. Several antioxidants have been proposed to counteract the harmful impact of ROS during semen cryopreservation. The antioxidant capability of quercetin has been verified in different animal species for providing valuable defence to sperm during the cryopreservation process. The beneficial properties of quercetin on various parameters of fresh and post‐thaw sperm in different species are clarified in this review. More in‐depth investigations are required to clarify quercetin's mechanism of action in different animal species.